PENGARUH PENILAIAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN: Survei Pada Marketplace Shopee - Hayuni, Okta Ros; Iskandar, Rhoma; Darmeinis, Darmeinis (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
The research aims to examine and analyze the influence of product rating and reviews on consumer purchasing decisions on the Shopee marketplace. The population in this study comprises the community residing in the Cilangkap Sub-Disctrict area. The sampling technique used is Non-Probability Sampling. This research adopts an associative quantitative approach. Data collection was carried out by distributing questionnaires, and data analysis to examine the relationship between variables was performed using simple linear regression analysis. The results show that product rating dan reviews have a positive and significant influence on purchasing decisions. This finding is supported by the regression analysis results, which yielded a significance value meeting the statistical criteria. Furthermore, the R-squared value indicates that product rating dan reviews are the main factor explaining the variation in purchasing decisions. It can be concluded that the higher the rating and the more positive the reviews given to a product, the greater the consumers tendency to make a purchase